ANALISIS MARJIN PEMASARAN CABAI RAWIT DI DESA TOLUAYA KECAMATAN BOLAANG UKI (Marketing Margin Analysis of Chili in Toluaya Village Bolaang Uki Sub District) - Devi Yulianti Umar; Celcius Talumingan; Paulus A. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
Chili is widely consumed by Toluaya people, so it is necessary to study the marketing system of chili, marketing margin and farmer's share in Toluaya Village. The objective of this study is to analyze the marketing margin of chili and farmer's share in Toluaya Village, for three months from August to September 2019. The types of data used are primary data and secondary data obtained through interviews using questionnaires. Sampling using purposive sampling method for farmer respondents and snowball sampling for intermediary traders.The research results showed that the zero-level channel marketing margin was Rp 0 per kilogram. The marketing margin for channel I level is Rp 15,000 per kilogram. The marketing margin for channel II level is Rp 20,000 per kilogram. The marketing margin for channel III level is Rp 50,000 per kilogram. The farmer's share in each of the chili marketing channels in Toluaya Village is obtained by channel zero level of 100%, channel I level of 76.9%, channel II level of 73.3% and channel III level of 54, 6%. In this research, it can be concluded that the marketing margin of chili in Toluaya Village is the biggest at channel III level, because channel III level has the highest level of economic efficiency. The farmer's share received by chili farmers in Toluaya Village, is the largest at the zero level channel, because the zero level channel is the shortest marketing channel for chili and is more efficient technically and economically, because of the percentage margin marketing is lowest and farmer's share is highest.Keywords: Chili, Marketing Margin, Farmer's Share